Effect of different concentrations of nitrate and phosphate on Geosmin and 2-Methylisoborneol production by some species of cyanobacteria - Fo'ad M. Alkam; Mysoon M. AL-Taee; Haider A. Alghanmi (Al-Qadisiyah Journal of Pure Science, 2018)
This study is considered the first of its kind in Iraq, It deals with compounds that never had been studied in Iraq called taste and odour compounds, most frequent were geosmin and 2-MIB. Two species were identified as producers for taste and odour compounds, the first was Phormidium retzii produced geosmin and Microcoleus vaginatus produced 2-MIB which were recorded for the first time in the world as a producer. The headspace solid phase microextraction method was used to extract these two compounds from aqueous solution, which were used for the first time in Iraq.Four concentrations of nitrate and phosphate were used (97, 350, 861 and 1500 Î¼gNO3-- N/L) and (12, 40, 400 and 870 Î¼gPO4 --P/L), for observing its effect upon the production of geosmin and 2-MIB by two cyanobacterial species. The maximal production of geosmin was 281.38 ng/l occurred at 861Î¼g NO3-N/L, whereas the higher production of 2-MIB was 296 ng/l occurred at the same concentration in the late of logarithmic phase. The high concentration of nitrate (1500 Î¼gNO3 --N/L) leaded to suppressed geosmin and 2-MIB productions. The maximal production of geosmin was 132.2 ng/l occurred at 870Î¼g PO4-P/L, whereas the higher production of 2-MIB was 167.2 ng/l occurred at the same concentration in the late logarithmic phase.